The Influence of Product Quality, Price and Service Quality on Consumer Satisfaction at Dapoer Marpoyan Jl. Kaharudin Nasution Pekanbaru - Harahap, Selfiana Handayani; Putri, Rosi Yuliani (First Ciera Publisher, 2024)
The purpose of this study was to determine the effect of Product Quality, Price and Service Quality on Consumer Satisfaction at Dapoer Marpoyan Jl. Kaharudin Nasution Pekanbaru. The sample in this study was 100 consumers. The data analysis used was validity test, reliability test, classical assumption test, multiple linear regression, hypothesis test and determination coefficient test. Based on the results of the study, it is known that the partial test (t-test) shows that the product quality variable is known to be tcount (5.893)> ttable (1.984) and Sig. (0.000) <0.05 and the service quality variable is known to be tcount (4.687)> ttable (1.984) and Sig. (0.000) <0.05. This means that the product quality and service quality variables have a significant effect on consumer satisfaction at Dapoer Marpoyan Pekanbaru. However, the price variable is known to be tcount (-8.719) <ttable (1.984) and Sig. (0.000) < 0.05. This means that the price variable does not have a significant effect on consumer satisfaction at Dapoer Marpoyan Pekanbaru. Simultaneously shows that product quality (X1), price (X2) and service quality (X3) simultaneously have an effect on consumer satisfaction at Dapoer Marpoyan Pekanbaru with the test results known F count (60.524) > F table (2.70) with a significance of 0.000 < 0.05. In terms of the coefficient of determination, the variables of product quality, price and service quality have an effect of 65.4% on consumer satisfaction while the remaining 34.6% are other factors not studied by the author.